2008
DOI: 10.17221/3/2008-pps
|View full text |Cite
|
Sign up to set email alerts
|

Cohabitation and intraleaf distribution of phytoseiid mites (Acari: Phytoseiidae) on leaves of Corylus avellana

Abstract: Kabíček J. (2008): Cohabitation and intraleaf distribution of phytoseiid mites (Acari: Phytoseiidae) on leaves of Corylus avellana. Plant Protect. Sci., 44: 32-36.Leaves from uncultivated and unsprayed hazelnut shrubs, Corylus avellana, were sampled from June to August 2005 to obtain information on the phytoseiid mite taxocenoses, population density and intraleaf distribution. Six phytoseiid mite species were identified, of which three, Kampimodromus aberrans, Euseius finlandicus and Neoseiulella tiliarum, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
0
7
0
2
Order By: Relevance
“…Grostal & O'Dowd 1994) and in the field (e.g. O'Dowd & Willson 1997; O'Dowd & Pemberton 1998), domatia alter the within‐leaf distribution of mites, including phytoseiids (O'Dowd & Willson 1997; Kabicek 2005), and have a positive population‐level effect on predaceous and fungivorous mites, elevating their survival and reproduction (e.g. Walter & O'Dowd 1992b; O'Dowd & Pemberton 1998; Monks et al.…”
Section: Discussionmentioning
confidence: 99%
“…Grostal & O'Dowd 1994) and in the field (e.g. O'Dowd & Willson 1997; O'Dowd & Pemberton 1998), domatia alter the within‐leaf distribution of mites, including phytoseiids (O'Dowd & Willson 1997; Kabicek 2005), and have a positive population‐level effect on predaceous and fungivorous mites, elevating their survival and reproduction (e.g. Walter & O'Dowd 1992b; O'Dowd & Pemberton 1998; Monks et al.…”
Section: Discussionmentioning
confidence: 99%
“…The three reports in Massachusetts (USA) were on insects: Graphiphora haruspica (Grote) and Spaelotis clandestine (Harris) (Noctuidae, Lepidoptera) (Treat 1975). Countries from which this species is reported are: Algeria (Athias-Henriot, 1958b); Austria (Bohm 1960;Ragusa and Ragusa 1997); Azerbaijan (Abbasova 1972);Canada (Nesbitt 1951;Herbert 1952;Chant et al 1974); Croatia (Tixier et al 2010); Czech Republic (Kabicek 2003;Kabicek and Rehakova 2004;Kabicek 2008Kabicek , 2010); Denmark (Hansen and Johnsen 1986); England (Nesbitt 1951;Chant 1955Chant , 1956Collyer 1956); France (Gunthart , 1960Rambier 1974;Kreiter and Brian 1987;Kreiter et al 2000;Tixier et al 2000;Arnault et al 2008); Georgia (Samsoniya 1977); Germany (Oudemans 1930;Dosse 1956aDosse , b, 1957Westerboer and Bernhard 1963;Thill 1964;Karg 1970Karg , 1971Karg , 1972Karg , 1975; Greece (Swirski and Ragusa 1976;Ragusa and Tsolakis 1998); Hungary (Kropczyńska and Jenser 1968;Bozai 1980;Dellei and Szendrey 1991;Sarospataki et al 1992;Bream and Bozai 1995;Bozai 1996...…”
Section: Neoseiulella Tiliarum (Oudemans) (Figure 5)mentioning
confidence: 99%
“…The majority of the examined leaflets (47.2%) were inhabited by a single mite species. Likewise, Kabíček (2008) reported that the presence of a single phytoseiid species per hazelnut leaf was observed most commonly under natural conditions. Only 12.8% of the examined leaflets were found to harbour two different species, the most common combination being e. finlandicus and N. aceri, detected on 8.4% of the leaflets.…”
Section: Resultsmentioning
confidence: 95%
“…The co-occurrence of more than three phytoseiid species per inspected leaflet has not been observed. Similarly, the cooccurrence of different phytoseiid mite species on leaves of Corylus avellana under natural conditions has seldom been observed (Kabíček 2008). Individual leaves, as distinctly demarcated habitats, allow the realization of opportunistic species interactions among phytoseiid mites.…”
Section: Resultsmentioning
confidence: 99%